自転車エルゴメータを用いた有負荷条件時の前腕義手ソケット内温湿度計測（第2報） - 大田, 弥史; 神田, 智基; 大西, 謙吾; 中村, 隆; 三田, 友記 (Transactions of Japanese Society for Medical and Biological Engineering, 2016)
Resin is the common material for upper limb prosthesis socket due to their ease and smoothness of forming curved surface to fit the residual limb shape. These socket are suitable for suspension and force transmission, however, the breathability and moisture permeability are low. To understand and moderate the inner socket hydrothermal characteristic of the upper limb prosthesis, it should be measured during operation. However, the measurement is not stable and non-uniform at such condition. Therefore, the objective is set to investigate the temperature and humidity inside the socket with non-amputee subject donning quasi-transradial prosthesis under lower limbs exercise condition. The experiment was conducted on 3 subjects donning socket during exercise using a bicycle ergometer under constant environmental temperature and humidity. As a result, the inner socket body surface temperature showed different characteristic then the resting condition and declined for the initial 8 minutes of the exercise and turned to increase.